Love Is Empire: A Cognitive Analysis of Metaphors of Empire in John Donne’s Love Poetry - SOHRABI, Zohreh; PIRNAJMUDDIN, Hossein; JANNESSARI, Zahra (Anafora, 2023)
The poetry of John Donne is replete with elaborate metaphors. As the products of an age of nascent imperialism and colonization, the metaphors he uses to describe the concept of love demonstrate his deep preoccupation with the question of imperial domain. These metaphors have mostly been studied in the light of his political and religious tendencies. However, according to cognitive poetics as a recent literary discipline, these metaphors are windows across the way the poet understands different concepts. Lakoff and Johnson argue that the metaphor is not merely a linguistic matter, but our very conceptual system is fundamentally metaphorical, and we understand the world metaphorically. A cognitive poetic approach will help us reveal how the poet constructs his metaphors cognitively, what are the internal structures of his metaphors, and what are the interrelations between these metaphors and the ideologies of the time. By combining insights from cognitive poetics and Edward Said’s views about culture and imperialism, we can better understand the world of love Donne creates in his poetry and its relations with the world outside.